p58IPK Is an Endogenous Neuroprotectant for Retinal Ganglion Cells - McLaughlin, Todd; Dhimal, Narayan; Li, Junhua; Wang, Joshua Jianxin; Zhang, Sarah Xin (Frontiers in Aging Neuroscience, 2018)
p58IPK is an endoplasmic reticulum (ER)-resident chaperone playing a critical role in facilitating protein folding and protein homeostasis. Previously, we have demonstrated that p58IPK is expressed broadly in retinal neurons including retinal ganglion cells (RGCs) and loss of p58IPK results in age-related RGC degeneration. In the present study, we investigate the role of p58IPK in neuroprotection by in vitro and in vivo studies using primary RGC culture and two well-established disease-relevant RGC injury models: retinal ischemia/reperfusion (I/R) and microbead-induced ocular hypertension. Our results demonstrate that in both in vivo models, p58IPK -/- mice exhibit significantly increased RGC loss compared to wild type mice. In vitro, p58IPK-deficient RGCs show reduced viability and are more susceptible to cell death induced by the ER stress inducer tunicamycin. Overexpression of p58IPK by adeno-associated virus (AAV) significantly diminishes tunicamycin-induced cell death in both wild type and p58IPK -/- RGCs. Interestingly, we find that loss of p58IPK leads to reduced mRNA expression, but not the protein level, of mesencephalic astrocyte-derived neurotrophic Factor (MANF), a neurotrophic factor that resides in the ER. Treatment with recombinant MANF protein protects R28 retinal neural cells and mouse retinal explants from tunicamycin-induced cell death. Taken together, our study suggests that p58IPK functions as an endogenous neuroprotectant for RGCs. The mechanisms underlying p58IPK’s neuroprotective action and the potential interactions between p58IPK and MANF warrant future investigation.